Psychosocial characteristics pattern correlated with suicidal ideation and non-suicidal self-injury among nurse staff: a latent profile analysis - Xuehua Li; Changmian Ding; Guizhi Li; Zhizhou Duan (BMC, 2024)
Abstract Background Nurses frequently endure elevated levels of psychosocial stress, which often correlates with an increased suicide risk. This study aimed to investigate the impact of latent psychosocial characteristic patterns on suicidal ideation and non-suicidal self-injury among nursing staff. Method Participants were recruited from the Dehong districts of Yunnan province, China, between July 11th and July 26th, 2022. Subgroups were identified using variables linked to suicidal ideation and non-suicidal self-injury, including perceived cognitive deficits, anxiety symptoms, depressive symptoms, resilience, social support, childhood trauma, loneliness, and sleep quality. Measurement tools included the Perceived Deficit Questionnaire-5-item (PDQ-5), Generalized Anxiety Disorder-7 items (GAD-7), Patient Health Questionnaire (PHQ-9), Connor-Davidson Resilience Scale-10 items (CD-RISC10), Multidimensional Scale of Perceived Social Support (MSPSS), Childhood Trauma Questionnaire-Short Form (CTQ-SF), Three-Item Loneliness Scale, and a single-item sleep quality scale. Results Latent profile analysis (LPA) revealed four distinct psychosocial characteristic patterns: "class 1," "class 2," "class 3," and "class 4." Compared to class 2, individuals in class 1 had a sixfold increased risk of suicidal ideation (OR = 6.59, 95%CI = 4.42-9.81) and a fivefold increased risk of non-suicidal self-injury (OR = 5.13, 95%CI = 3.38-7.78). Similarly, class 4 individuals had twice the risk of suicidal ideation (OR = 2.13, 95%CI = 1.25-3.62) and non-suicidal self-injury (OR = 2.13, 95%CI = 1.25-3.65) compared to class 2. Conversely, class 3 individuals had a lower risk of suicidal ideation (OR = 0.21, 95%CI = 0.11-0.42) and non-suicidal self-injury (OR = 0.15, 95%CI = 0.07-0.36) than class 2. Additionally, divorced/other marital status individuals had a higher risk of suicidal ideation (OR = 2.34, 95%CI = 1.02-5.35) and non-suicidal self-injury (OR = 2.58, 95%CI = 1.01-6.65) compared to married individuals, while unmarried individuals had a lower risk of suicidal ideation (OR = 0.58, 95%CI = 0.37-0.91). Conclusions The study identified eight important psychosocial factors divided into four latent pattern classes. Individuals in "class 1" and "class 4" were more likely to have a higher risk of suicidal ideation and non-suicidal self-injury, while those in "class 3" were more likely to have a lower risk of both outcomes. It is suggested that further research should focus on "class 1" and "class 4" for targeted intervention.